Platelet count before peripheral blood stem cell mobilization is associated with the need for plerixafor but not with the collection result - Bärtsch, Marc-Andrea; Kriegsmann, Katharina; Bruckner, Thomas; Hundemer, Michael; Kriegsmann, Mark; Ho, Anthony Dick; Goldschmidt, Hartmut; Wuchter, Patrick (Transfusion medicine and hemotherapy, 2018)
Background: A low platelet count before mobilization has recurrently been identified as risk factor for poor mobilization. Methods: To determine the relevance of this finding for peripheral blood stem cell (PBSC) mobilization, including pre-emptive or rescue plerixafor in the case of poor mobilization, we retrospectively analyzed all patients undergoing PBSC collection at our institution between January 2014 and December 2015 (n = 380). Results: In total, 99% of the patients (377/380) successfully collected a minimum of 2 × 10 6 CD34+ cells/kg body weight sufficient for a single transplant. Rescue or pre-emptive plerixafor was administered to 11% of the patients (42/380). No correlations between the platelet count before mobilization and the number of peripheral blood CD34+ cells or the CD34+ cell collection result were detected in the entire population or the subgroups according to diagnosis (newly diagnosed multiple myeloma, relapsed multiple myeloma, lymphoma, amyloid light-chain amyloidosis, sarcoma, or germ cell tumor). However, patients requiring pre-emptive or rescue plerixafor had a significantly lower platelet count before mobilization (217/nl vs. 245/nl; p = 0.004). Conclusion: With the current state of the art PBSC mobilization strategies, the platelet count before mobilization was not associated with the CD34+ cell collection result but was associated with the need for pre-emptive or rescue application of plerixafor.
Gesehen am 07.08.2019
Published online: October 4, 2017